Life as Paradigm of Knowledge. What Use of Hegel in the Age of the Environmental Crisis? - Achella, Stefania (ETHICS IN PROGRESS, 2024)
This paper aims to show to what extent the normativity of organic life that emerged from the natural sciences of Hegel’s time influenced the structuring of his speculative approach. In the first part, the eighteenth-century paradigm shift in the natural sciences is investigated as marking the transition from a physics-based worldview to a biology-based one. This shift argues strongly against the reduction of nature to mechanism and provides an adequate model for analysing the functioning of all other complex systems and, above all, the functioning of reason. In the second part, the consequences of such a shift are evaluated with respect to Hegel’s idealism, especially in relation to the categories of organism and purpose. They are the core elements for understanding not only the mode of living but also that of thinking. In the last part, we identify Hegel’s philosophy as a “living ontology,” an ontology that keeps pace with reality by modifying its categories accordingly. From this point of view, Hegel’s idealism can be compatible with a new idea of the relationship between human beings and the environment, in the direction of a relational ontology. The paper then focuses on the legacy of this re-reading of Hegel’s philosophy in the contemporary debate on ecological thinking that attempts to answer the question raised in the discussion on the environmental crisis and Anthropocene.